Synthesis and Characterization of Sot-Gel Derived Single-Phase PZT Nanoparticles in Aqueous Polyol Solution - Zak, A.K.; Abd Majid, Wan Haliza; Darroudi, M. (2010)
Lead zirconate titanate nanoparticles (PZT-NPs) were synthesized by the modified sol-gel method in aqueous poly ethylene glycol (PEG) solutions. The mixed metal alkoxide precursor was prepared by moderate refluxing using lead acetate, zirconium n-propoxide, titanium iso-propoxide and acetic acid in aqueous PEG media. The properties of PZT-NPs were studied as a function of calcination temperatures. Results from the Fourier transform infrared (FTIR), powder X-ray diffraction (XRD) and thermal analysis (TGA/DTA), indicated that the single-phase perovskite PZT-NPs were obtained after heat treatment at temperature of 650 degrees C. The average particle size of synthesized PZT-NPs was calculated by using the Debye-Scherrer formula and was found to be around 25 nm, which was in a good agreement with the microstructures obtained performed by scanning electron microscopy (SEM) and transition electron microscopy (TEM).